Devices and desires: science fiction, fantasy and disability in literature for young people - Stemp, Jane (Disability Studies Quarterly, 2004)
Characters with disabilities have a surprisingly long history in science and fantasy fiction, but the date of a book's publication is no guide to the manner in which the characters with disabilities are portrayed. This paper studies, from a personal rather than an academic viewpoint, fantasy and science fiction books in the writer's own collection, and discusses some recurrent themes and motifs, with possible reasons for their use.